2011
DOI: 10.1002/jmv.23182
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy of potential antiviral resistance mutation profiles within the HBV reverse transcriptase between nucleos(t)ide analogue‐untreated and ‐treated patients with chronic hepatitis B in a hospital in China

Abstract: Little is known about the discrepancy of the potential antiviral resistance mutation profiles within the hepatitis B virus (HBV) reverse transcriptase (RT) between nucleos(t)ide analogue (NA)-untreated and -treated patients with chronic hepatitis B. Full-length HBV RT sequences from 59 NA-treated and 105 NA-untreated Chinese patients were amplified and sequenced. Forty-two potential NA resistance (NAr) mutation sites were screened within these 164 RT sequences. The NAr mutation prevalence and frequency in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 48 publications
3
18
0
Order By: Relevance
“…These finding were supported by previous studies [24,25]. The mutations at rt169 and rt184 residues responsible for ETV resistance were not detected.…”
Section: Discussionsupporting
confidence: 88%
“…These finding were supported by previous studies [24,25]. The mutations at rt169 and rt184 residues responsible for ETV resistance were not detected.…”
Section: Discussionsupporting
confidence: 88%
“…[15] The subject with rtI169L mutation had no history of entecavir treatment. Recently, Li et al, [7] showed rtI169L as primary drug resistance mutation associated with adefovir treatment. This report supports our fi nding and illustrates rtI169L mutation to be associated with adefovir resistance.…”
Section: Discussionmentioning
confidence: 98%
“…[5] The primary adefovir-resistant mutations are rtN236T and rtA181T/V. [6] Recently, Li et al, [7] showed a novel rtI169L mutation as a primary drug resistance mutation associated with adefovir monotherapy. The cumulative probability of mutations associated with resistance to adefovir is 0%, 3%, 11%, 18% and 29% after 1, 2, 3, 4 and 5 years, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…In recent studies conducted with non-treated patients in different countries, it was shown that the frequencies of HBV strains which had clinically important drug resistance mutation (NA resistance) were between 0.5% and 1% (17,18,19,20,21,22,23,24,25 (29) evaluated 30 CHB patients who were not previously treated and they determined HBV NA resistance-related mutations in 3 of them (10%).…”
Section: Discussionmentioning
confidence: 99%